Techno-economic environmental assessment of hybrid renewable energy system in India - K. M. Venkatachalam; V. Saravanan (Institute of Advanced Engineering and Science, 2021)
The co-ordination of non-conventional energy technologies such as solar, wind, geothermal, biomass and ocean are gaining significance in India due to more energy requirements and high greenhouse gas emission. In this assessment, the sustainability of emerging the gird isolated hybrid solar photovoltaic (PV)/wind turbine (WT)/diesel generator (DG)/battery system for Arunai Engineering College, India building is evaluated. The techno-economic and environmental research was inspected by HOMER Pro software by choosing the optimal combination depends on size of the components, renewable fraction, net present cost (NPC), cost of energy (COE) and greenhouse gas (GHG) emission of the hybrid system. From the acquired outcomes and sensitivity investigation, the optimal PV-WT-DG-battery combination has a NPC of 28.944.800 and COE 0.1266/kWh, with an operating cost of 256.761/year. The grid isolated hybrid system is environmentally pleasant with a greenhouse gas emission of 2.692 kg/year with renewable fraction of 99.9%.